Black phosphorus-doped silk fibroin coating improves osteogenesis for ameliorative graft-bone healing of polyethylene terephthalate artificial ligaments - Wei, Jianxing; Wu, Xiulin; Wu, Jia; Zhang, Tianlun; Zhao, Jinzhong; Cai, Jiangyu (Frontiers in Bioengineering and Biotechnology, 2026)
This study aimed to investigate the effect of black phosphorus-doped silk fibroin (BP/SF) coating on graft-bone healing of artificial ligaments made from polyethylene terephthalate (PET). A BP/SF-coated PET artificial ligament (BP/SF-PET) was prepared, and its surface characteristics were examined using transmission electron microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray diffraction. The cytocompatibility and osteogenic induction ability of the BP/SF-PET ligaments were evaluated in vitro. In addition, uncoated PET (PET group, n = 15) and BP/SF-coated PET (BP/SF-PET group, n = 15) artificial ligaments were randomly applied for anterior cruciate ligament reconstruction in rabbits. Micro-computed tomography (CT), and histological, immunofluorescent, and biomechanical analyses were performed 6 and 12 weeks postoperatively to evaluate graft-bone healing in vivo. Material characterization results confirmed the presence of BP/SF coating on the PET surface. In vitro experiment findings showed that BP/SF coating enhanced the viability of MC3T3-E1 preosteoblasts and L929 fibroblasts, and osteogenic differentiation of MC3T3-E1 preosteoblasts. The BP/SF-PET group exhibited stronger Alizarin Red staining and greater expression of genes involved in osteogenesis (COL1, OCN, and OPN) than the PET group. Micro-CT and histological analyses showed enhanced graft osseointegration in the BP/SF-PET group, as evidenced by new bone and fibrocartilage tissues developed at the graft-bone interface 12 weeks postoperatively. Accordingly, the histological scores in the BP/SF-PET group were higher. Immunofluorescent staining revealed that positive staining cells for CD68 at 6 weeks were lower and for Wnt-5a and β-catenin at 12 weeks were higher in the BP/SF-PET group than those in the PET group. Biomechanical analysis indicated that, at 12 weeks postoperatively, the BP/SF-PET group showed a notably higher failure load and stiffness compared to the PET group. To conclude, BP/SF coating significantly improved the biocompatibility and osteogenesis of PET artificial ligament, facilitating graft-bone integration after anterior cruciate ligament reconstruction via the Wnt/β-catenin signaling pathway.